PERENCANAAN STRATEGI KOMUNIKASI PEMASARAN TERPADU (IMC) DALAM MENDORONG KONVERSI PENGGUNAAN PRODUK BY.U BY TELKOMSEL SEBAGAI PROJECT MANAGER - Nayyara Aisyah Mahdiya; Djoko Setyabudi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
By.U is a digital cellular service launched by Telkomsel that specifically targets Generation Z andyoung digital users. Despite its positioning as a youth-oriented digital provider, the level of by.U usageamong high school and vocational school students in Semarang remains relatively low. A preliminarysurvey conducted among 814 students from four schools affiliated with Telkomsel’s educationalplatform, Skul.id, revealed that only 5,7% or 46 students were active users of the by.U SIM card. Inaddition, the survey indicated a relatively high level of perceived risk toward the service at 52,2%,accompanied by low purchase intention of only 20,8%. To address this issue, an Integrated MarketingCommunication (IMC) campaign was designed and implemented through two main programs, namelythe “by.U On The Move” and the “by.U Inter-School Digital Challenge.” The campaign utilized acombination of offline activation and digital communication strategies, including media relations,social media marketing, influencer marketing, and event marketing. These activities were designed toencourage students to move through the stages of attention, interest, desire, and action, following theHierarchy of Effects model in marketing communication. The implementation of the campaigndemonstrated significant results. The perceived risk among students decreased from 52,2% to 19,5%,indicating improved trust toward the service. Meanwhile, purchase intention increased from 20,8% to72,8%. In addition, the number of active by.U users increased from 46 students to 118 students acrossthe targeted schools.As a Project Manager, the author was responsible for planning, coordinating, and supervising theentire campaign process, from the planning stage to implementation and evaluation. This reportdocuments the effectiveness of the implemented communication strategies and provides practicalinsights for future integrated marketing communication campaigns targeting youth audiences.